2007
DOI: 10.4103/1319-3767.32182
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis B virus infection in the Gezira State of Central Sudan

Abstract: This study shows that prevalence of HBV infection is high in the studied population and it is hoped that introduction of blood screening and vaccination against HBV would decrease the carrier pool in the next few years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 2 publications
4
31
3
Order By: Relevance
“…The current study demonstrated the case fatality rates of 16.7% among HIV positive VL cases which is closer to estimates from Ethiopia that showed a mortality rate of 15.5% among VL/HIV co-infected patients treated with SSG [23]. However, it is inconsistent with 39.3% that reported by Mengistu et al, among VL/HIV co-infection [24]. VL/HIV co-infection has important clinical implications, as VL accelerates progression to AIDS by stimulating replication of the HIV.…”
Section: Resultscontrasting
confidence: 54%
“…The current study demonstrated the case fatality rates of 16.7% among HIV positive VL cases which is closer to estimates from Ethiopia that showed a mortality rate of 15.5% among VL/HIV co-infected patients treated with SSG [23]. However, it is inconsistent with 39.3% that reported by Mengistu et al, among VL/HIV co-infection [24]. VL/HIV co-infection has important clinical implications, as VL accelerates progression to AIDS by stimulating replication of the HIV.…”
Section: Resultscontrasting
confidence: 54%
“…Sudan is classified among the African countries with high HBV endemicity. The reported prevalence of HBV chronic infection, characterized by the detectable level of HBV surface antigen (HBsAg), varied from region to region and ranged between 5 and 7% in the general population (1,13,28,31) and 26% in hospital outpatients (25). The prevalence of adults having been in contact with HBV and identified by the presence of anti-core antibodies (anti-HBc) was high, ranging between 47.5 and 67% (25,28).…”
Section: Sudan Is a Highly Endemic Area For Hepatitis B Virus (Hbv)mentioning
confidence: 99%
“…The reported prevalence of HBV chronic infection, characterized by the detectable level of HBV surface antigen (HBsAg), varied from region to region and ranged between 5 and 7% in the general population (1,13,28,31) and 26% in hospital outpatients (25). The prevalence of adults having been in contact with HBV and identified by the presence of anti-core antibodies (anti-HBc) was high, ranging between 47.5 and 67% (25,28). The introduction of vaccination and the screening of blood and blood products during the past 8 years is expected to reduce the rate of HBV infection and the carrier pool (28).…”
mentioning
confidence: 99%
“…There is a significant correlation between occupational hazards and infection and carrier rates among HCWs in Public Hospitals in Khartoum State, Sudan [16]. Among general population in Gezira State, Central Sudan, the prevalence of infection (positive Anti-HBcore) and carrier (positive HBsAg) is 47.5% and 6.9% respectively [17][18][19][20]. HBV is highly endemic in Sudan, where it is ranked as the second cause of acute liver failure and the main cause of hepatocellular carcinoma [21].…”
Section: Background Informationmentioning
confidence: 99%